DNA Double Strand Breaks and Chromosomal Translocations Induced by DNA Topoisomerase II - Gómez-Herreros, Fernando (Frontiers in Molecular Biosciences, 2019)
DNA double strand breaks (DSBs) are the most cytotoxic lesions of those occurring in the DNA as can lead to cell death or result in genome mutagenesis and chromosomal translocations. Although most of these rearrangements have detrimental effects for cellular survival, single events can provide clonal advantage and result in abnormal cellular proliferation and cancer. The origin and the environment of the DNA break or the repair pathway are key factors that influence the frequency at which these events appear. However, the molecular mechanisms that underlie the formation of chromosomal translocations remain unclear. DNA topoisomerases are essential enzymes present in all cellular organisms with critical roles in DNA metabolism and that have been linked to the formation of deleterious DSBs for a long time. DSBs induced by the abortive activity of DNA topoisomerase II (TOP2) are ‘trending topic’ because of their possible role in genome instability and oncogenesis. Furthermore, transcription associated TOP2 activity appears to be one of the most determining causes behind the formation of chromosomal translocations. In this review, we will summarise the origin of recombinogenic TOP2 breaks and the determinants behind their tendency to translocate.